2017
DOI: 10.5603/cj.a2017.0002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 180 mg ticagrelor loading dose on myocardial necrosis in patients undergoing elective percutaneous coronary intervention: A preliminary study

Abstract: (Cardiol J 2017; 24, 1: 15-24)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…There were substantial numbers of patients with asymptomatic rises in troponin after PCI, but no evidence that ticagrelor was more effective than clopidogrel in attenuating troponin release, suggesting that the extent of myocardial injury induced by PCI is not usually sensitive to levels of platelet P2Y 12 inhibition in a low-risk population. This observation is consistent with a previously reported small elective PCI study, 31 but contrasts with another small study that demonstrated a reduced rate of MI with ticagrelor compared to clopidogrel. 32 Larger clinical outcomes studies are in progress that will provide more definitive data on this comparison (NCT02617290 and NCT02548611).…”
Section: Discussionsupporting
confidence: 92%
“…There were substantial numbers of patients with asymptomatic rises in troponin after PCI, but no evidence that ticagrelor was more effective than clopidogrel in attenuating troponin release, suggesting that the extent of myocardial injury induced by PCI is not usually sensitive to levels of platelet P2Y 12 inhibition in a low-risk population. This observation is consistent with a previously reported small elective PCI study, 31 but contrasts with another small study that demonstrated a reduced rate of MI with ticagrelor compared to clopidogrel. 32 Larger clinical outcomes studies are in progress that will provide more definitive data on this comparison (NCT02617290 and NCT02548611).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, our results suggest that ticagrelor has no superior efficacy in the prevention of ischemic complications of RA, such as no reflow/slow flow. Few data are available about the effect of ticagrelor on post PCI troponin rise in stable CAD patients, and results were controversial until the ALPHEUS trial [ 7 , 8 , 9 ]. This trial did not show any difference between ticagrelor and clopidogrel in elective PCI on ischemic end points in a high-risk population for ischemic events despite relevant differences in pharmacodynamic effects among both arms.…”
Section: Discussionmentioning
confidence: 99%
“…The ALPHEUS (Assessment of Loading With the P2Y12 Inhibitor Ticagrelor or Clopidogrel to Halt Ischemic Events in Patients Undergoing Elective Coronary Stenting) study failed to demonstrate ticagrelor superiority over clopidogrel in reducing periprocedural myocardial necrosis in stable coronary patients undergoing high-risk elective PCI. Data comparing ticagrelor with clopidogrel in stable coronary artery disease (CAD) patients are limited, and this drug has never been specifically evaluated in patients treated with rotational atherectomy (RA) [ 7 , 8 , 9 ]. RA facilitates PCI for de novo severely calcified or unexpandable lesions, which are increasingly prevalent in the elderly population.…”
Section: Introductionmentioning
confidence: 99%